2010
DOI: 10.1136/emj.2009.080267
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Ottawa Knee Rule in Iran: a prospective study

Abstract: Prospective validation has shown that the OKR is a highly sensitive tool for detecting knee fractures and has the potential to reduce the number of radiographs in patients with acute knee injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(38 reference statements)
1
3
1
Order By: Relevance
“…In Similarly, the specificity matching in accordance (42.02%) to our study has been 2,5,12,19 reported by few other studies as well. According to our study, implemen ng the OKR would have resulted in an overall reduc on in the use of radiographs by 37.61%.…”
Section: Discussionsupporting
confidence: 93%
“…In Similarly, the specificity matching in accordance (42.02%) to our study has been 2,5,12,19 reported by few other studies as well. According to our study, implemen ng the OKR would have resulted in an overall reduc on in the use of radiographs by 37.61%.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the 43% potential reduction in radiography if the OKR was correctly applied is consistent with studies performed in Canada, Iran and Spain, which calculated reductions of 31.2%, 41% and 49%, respectively. 6,17,19 Our value is, however, higher than the rate in the original report by Stiell and colleagues (26.4%). 1 Finally, although the patient's time spent in ED was not specifically examined in our study, using the OKR could shorten the waiting time for our patients in ED.…”
Section: Discussioncontrasting
confidence: 78%
“…Since the development of the OKR in 1995, 2 its excellent sensitivity (near 100%) has been argued and found indisputable across many countries. 1,[4][5][6][7][8]17 However, few published studies have investigated the local generalisability of the rule, particularly in Australia. Our retrospective clinical audit evaluated OKR performance and referrer compliance in a tertiary hospital in South Australia.…”
Section: Discussionmentioning
confidence: 99%
“…• Not reported • 100%, 42.8%, 50% [190] • 95%, 44%, 50% [191] • Not reported * A systematic review study. The mixed evidence protocol is based on four steps.…”
Section: Predictive Performance Usability and Post-implementation Imp...mentioning
confidence: 99%